1990
DOI: 10.1161/01.cir.81.3.914
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced desensitization of beta-adrenoceptor function in humans. Subtype-selective reduction in beta 1- or beta 2-adrenoceptor-mediated physiological effects by xamoterol or procaterol.

Abstract: We investigated the effects of f%- (procaterol 2X50 jig/day for 9 days) and B1-(xamoterol 2 x200 mg/day for 14 days) adrenoceptor agonists on lymphocyte f%-adrenoceptor density and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…In our data, a similar result was obtained [8], although the beta-receptor assay was carried out using peripheral lymphocytes [34]. However, since the changes in receptor density may occur in a week [9,32], such a beneficial long-term effect cannot be explained by upregulation only. Thus, we have recently studied the changes in cyclic AMP production of the peripheral lymphocyte by in-vitro isopreterenol or forskolin loading before and after the administration [8] and withdrawal [10] of metoprolol.…”
Section: Fig 4 a Comparison Of Groups I (Beta-blocker Group) And Grsupporting
confidence: 82%
See 1 more Smart Citation
“…In our data, a similar result was obtained [8], although the beta-receptor assay was carried out using peripheral lymphocytes [34]. However, since the changes in receptor density may occur in a week [9,32], such a beneficial long-term effect cannot be explained by upregulation only. Thus, we have recently studied the changes in cyclic AMP production of the peripheral lymphocyte by in-vitro isopreterenol or forskolin loading before and after the administration [8] and withdrawal [10] of metoprolol.…”
Section: Fig 4 a Comparison Of Groups I (Beta-blocker Group) And Grsupporting
confidence: 82%
“…What kind of beta blocker can produce a favorable effect in dilated cardiomyopathy? We employed a cardioselective beta blocker without intrinsic sympathetic activity (ISA), metoprolol, in this study, since beta-adrenoceptor antagonists subtypes selectively regulate cardiac beta-receptor subtypes [31][32][33]. Ikram et al [15] employed acebutolol, which has ISA, and reported an adverse effect.…”
Section: Fig 4 a Comparison Of Groups I (Beta-blocker Group) And Grmentioning
confidence: 99%
“…Over a longer time period24, the vagolytic influence of EPI may dampen the peripheral capability of cholinergic anti-inflammatory pathways. A persistent EPI induced vagolytic effect would potentially heighten pro-inflammatory activity as β-2 receptor activity decreases70 and may permit an exaggerated immune response to additional inflammatory stimuli. A longer EPI infusion may be revealing since it is yet unknown whether the vagolytic effect of EPI persists or attenuates over time.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately the only β 1 ‐adrenoceptor selective agonist currently available for oral use in humans is xamoterol which is a partial β 1 ‐adrenoceptor agonist [ 5]. We have previously shown, in healthy volunteers, that following 2 weeks treatment with xamoterol cardiovascular β 1 ‐adrenoceptor‐mediated effects (exercise‐induced increase in heart rate and isoprenaline induced increase in systolic blood pressure) are attenuated [ 6]. This could be due to desensitization; it could also be due to an antagonist effect of the partial agonist xamoterol.…”
Section: Introductionmentioning
confidence: 99%